Answer:
16/1 I think
Step-by-step explanation:
ANSWER
The correct answer is C
EXPLANATION
The given triangle is a right triangle. Since two angles are equal, it is a right isosceles triangle.
This implies that, x=8 units.
Using Pythagoras Theorem,
![{y}^{2} = {8}^{2} + {8}^{2}](https://tex.z-dn.net/?f=%20%7By%7D%5E%7B2%7D%20%20%3D%20%20%7B8%7D%5E%7B2%7D%20%20%2B%20%20%7B8%7D%5E%7B2%7D%20)
This implies that:
![{y}^{2} = 64 + 64](https://tex.z-dn.net/?f=%7By%7D%5E%7B2%7D%20%20%3D%2064%20%20%2B%20%2064)
![{y}^{2} =128](https://tex.z-dn.net/?f=%7By%7D%5E%7B2%7D%20%20%3D128)
Take positive square root,
![{y} = \sqrt{128}](https://tex.z-dn.net/?f=%7By%7D%20%20%3D%20%20%5Csqrt%7B128%7D%20)
![{y} = 8 \sqrt{2}](https://tex.z-dn.net/?f=%7By%7D%20%20%3D%208%20%5Csqrt%7B2%7D%20)
The correct answer is C
Yes 7.5 is clearly the answer here
Arithmetic sequences have a common difference between consecutive terms.
Geometric sequences have a common ratio between consecutive terms.
Let's compute the differences and ratios between consecutive terms:
Differences:
![0.4-0.2 = 0.2,\quad 0.6-0.4=0.2,\quad 0.8-0.6=0.2,\quad 1-0.8=0.2](https://tex.z-dn.net/?f=0.4-0.2%20%3D%200.2%2C%5Cquad%200.6-0.4%3D0.2%2C%5Cquad%200.8-0.6%3D0.2%2C%5Cquad%201-0.8%3D0.2)
Ratios:
![\dfrac{0.4}{0.2}=2,\quad \dfrac{0.6}{0.4} = 1.5,\quad \dfrac{0.8}{0.6} = 1.33\ldots, \quad\dfrac{1}{0.8}=1.25](https://tex.z-dn.net/?f=%5Cdfrac%7B0.4%7D%7B0.2%7D%3D2%2C%5Cquad%20%5Cdfrac%7B0.6%7D%7B0.4%7D%20%3D%201.5%2C%5Cquad%20%5Cdfrac%7B0.8%7D%7B0.6%7D%20%3D%201.33%5Cldots%2C%20%5Cquad%5Cdfrac%7B1%7D%7B0.8%7D%3D1.25)
So, as you can see, the differences between consecutive terms are constant, whereas ratios vary.
So, this is an arithmetic sequence.
Answer:
A
Step-by-step explanation:
![\frac{(3x^{2} )^\frac{1}{2} }{3^\frac{1}{2} } =3](https://tex.z-dn.net/?f=%5Cfrac%7B%283x%5E%7B2%7D%20%29%5E%5Cfrac%7B1%7D%7B2%7D%20%7D%7B3%5E%5Cfrac%7B1%7D%7B2%7D%20%7D%20%3D3)
![(3x^2)^\frac{1}{2} = 3^\frac{1}{2} x](https://tex.z-dn.net/?f=%283x%5E2%29%5E%5Cfrac%7B1%7D%7B2%7D%20%3D%203%5E%5Cfrac%7B1%7D%7B2%7D%20x)
Remember that
x^(b-c)
Using that
=3^(1/2x-1/2)=3^((x-1)/2)
![3^\frac{x-1}{2} =3^1](https://tex.z-dn.net/?f=3%5E%5Cfrac%7Bx-1%7D%7B2%7D%20%3D3%5E1)
So we can say:
, because the bases are the same
We can multiply both sides of the equation by 2. We get x-1=2, and x=3. Which is A.